Applying informational entropy to the field of metallurgy - C. Oprean; C. Tănăsescu; G. Dobrotă (Metalurgija, 2016)
This article aims at analysing whether the field of metallurgy in Romania is informationally efficient or not. This field is important for the real Romanian and world-wide economy, that is why the answer to this dilemma is important, and it will determine the investment behaviour of portfolio managers. The Shannon Entropy is our measure for the informational efficiency of the field of metallurgy. The results obtained indicate that the field of metallurgy in Romania is characterized by a weak informational efficiency. Perhaps the most important effect of this result is the impossibility to make predictions in this field. In this context, a technical or chartist analysis is useless.